Low Intensity Laser Irradiation and Growth Factors Influence Differentiation of Adipose Derived Stem Cells into Smooth Muscle Cells in a Coculture Environment over a Period of 72 Hours - Bernard Mvula; Heidi Abrahamse (International Journal of Photoenergy)
Stem cells have the ability to self-renew and differentiate into several specialised cells. Low intensity laser irradiation (LILI) has been shown to have positive effects on cells including adipose derived stem cells (ADSCs). Growth factors such as retinoic acid and transforming growth factor (TGF-β1) play significant roles in the differentiation of cells. This study aimed at investigating the role of LILI and growth factors on differentiation of adipose derived stem cells cocultured with smooth muscle cells (SMCs). The study used isolated human adipose derived stem cells and smooth muscle commercial cells (SKUT-1). The cells were cocultured directly in the ratio 1 : 1 using the established methods with and without growth factors (retinoic acid and TGF-β1) and then exposed to LILI at a wavelength of 636 nm with 5 J/cm2 using a diode laser. The cellular proliferation and expression of the both cell type markers were assessed using optical density and flow cytometry at 24 h and 72 h. The study showed that LILI increased the proliferation of cocultured cells. The expression of the smooth muscle cell markers increased in the coculture groups that were exposed to LILI in the presence of growth factors while those of the ADSCs decreased.